Scientific Attitude Analysis On Students In Class Xi-Ipa At Sma Negeri 2 Bilah Hulu Regarding Human Blood Circulation System Material - Dwy Santi; Risma Delima Harahap; Sakinah Ubudiyah Siregar (University of Science and Computer Technology, 2023)
Attitude is a tendency to behave and may be viewed as an individual's response to a stimulus. Althoughattitudes toward biology, particularly the human circulatory system, can be represented by the acceptanceor rejection of certain biological objects. This research aims to determine the attitudes of high schoolstudents at SMA Negeri 2 Bilah Hulu towards biology subjects, particularly the material on the humancirculatory system. This research employed a qualitative strategy and descriptive approaches. The findingsof this survey indicate that the indicator of pleasure in studying biology is 78.30%, the indication ofcuriosity is 82.92%, the indicator of interest in extending biology time is 80.90%, and the indicator ofinterest in a career in biology is 79.89%. This research concludes that students have the highest positiveattitude toward the indicator of curiosity, while they have the least positive attitude toward the indicatorof enjoyment in learning biology.